The Internalization of the Yassirū Hadith in Self and Social Communication to Foster Life Optimism - Saskia Afridah; Maghrisul Akhiroh Syam; Suke Indah Khumaero; Lola Yuanda Arlinza; Al Khafi Al Khafi (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2026)
An ideal life is often hampered by the burden of stress and overthinking due to environmental demands and excessive self-expectations, especially in the younger generation. The hadith yassiru wala tu'assiru, wabasysyiru wala tunaffiruu offers a relevant spiritual and psychological foundation to overcome such pressure through the principle of ease and the giving of good news. This study aims to analyze the application of the values in the hadith as a way to deal with existing problems in dealing with life pressures through a communication perspective. This research uses a qualitative method with a library research approach. The data analysis technique used is content analysis with steps of data reduction, data presentation, and conclusion drawn. The results of the study show that the internalization of the hadith includes two dimensions: first, intrapersonal communication, in which individuals are able to build a positive dialogue with themselves and God to achieve inner peace. Second, interpersonal communication, which emphasizes behavior that facilitates other people's affairs and builds a supportive and solution-oriented social ecosystem. The contribution of this research is to provide a practical framework based on Islamic teachings for individuals to reduce anxiety through changing communication patterns, while offering a new perspective in the literature on Islamic counseling guidance related to stress management.